The Valuable Reference of Live Birth Rate in the Single Vitrified-Warmed BB/BC/CB Blastocyst Transfer: The Cleavage-Stage Embryo Quality and Embryo Development Speed - Shen, Xi; Long, Hui; Gao, Hongyuan; Guo, Wenya; Xie, Yating; Chen, Di; Cong, Yanyan; Wang, Yun; Li, Dongying; Si, Jiqiang; Zhao, Leiwen; Lyu, Qifeng; et al. (Frontiers in Physiology, 2020)
Background: It is unclear whether we should focus attention on cleavage-stage embryo quality and embryo development speed when transferring single particular grade vitrified-warmed blastocysts, especially in poor-quality blastocysts (grade ‘C’). Method: This retrospective study considered 3386 single vitrified-warmed blastocyst transfer cycles from January 2010 to December 2017. They were divided into group 1 (AA/AB/BA, n = 374), group 2 (BB, n = 1789), group 3 (BC, n = 901) and group 4 (CB, n = 322). The effects of cleavage-stage embryo quality and embryo development speed were measured in terms of clinical pregnancy and live birth rates in each group. Results: Pregnancy outcomes showed a worsening trend from groups 1 to 4; the proportion of embryos with better cleavage-stage quality and faster development speed decreased. In group 1, only the blastocyst expansion degree 3 was a negative factor in the clinical pregnancy rate (Odds ratio (OR) [95% confidence interval (CI)]: 0.233[0.091-0.595]) and live birth rate (0.280[0.093-0.884]). In the other groups (BB, BC and CB), blastocysts frozen on day 5 had significantly better clinical pregnancy outcomes than those frozen on day 6 :1.373 [1.095–1.722] for group 2, 1.523 [1.055–2.197] for group 3, and 3.627 [1.715–7.671] for group 4. The live birth rate was: 1.342 [1.060–1.700] for group 2, 1.544 [1.058–2.253] in group 3, 3.202 [1.509–6.795] in group 4, all P<0.05). The degree of blastocoel expansion three for clinical pregnancy rate in group 2 (0.350 [0.135–0.906], P<0.05) and day3 blastomere number (> 7) for live birth rate in group 4 (2.455 [1.190–5.063], P<0.05) were two important factors. Conclusions: We should consider choosing BB/BC/CB grade blastocysts frozen on day 5, CB grade blastocysts with day 3 blastomere number (>7) and AA/AB/BA grade blastocysts with degrees of expansion (≥4) to obtain better pregnancy outcomes.